Evaluation of the Availability and Feasibility of Main Land Side Facilities at the Bolok Ferry Port in Kupang City, East Nusa Tenggara Province - Umroh, Atika Khoirul; Pusriansyah, Ferdinand; Triwahyuni, Siti Nurlaili; Sari, Vita Permata; Fitriani, Prastiwi Desy (IWJ : Inland Waterways Journal, 2023)
Construction and improvement of basic land-side facilities at the Bolok Ferry Port can support the smooth flow of mobilization of goods and passengers to optimize port operations. The aim of this research is to determine the existing conditions and analyze the need for basic land side facilities at the Bolok Ferry Port and to find out the location of the planned placement of main land side facilities based on the provisions of the applicable regulations. This research is a quantitative descriptive research, namely to determine the need for several basic facilities on the land side based on KM Number 52 of 2004 concerning the Implementation of Ferry Ports. The research results obtained show that it is necessary to increase the area of ​​the passenger terminal by 396 m2, repair and re-placement of vehicle weighers, increase the length of the way for passengers entering/exiting the ship (gangway) which directly connects to the ship's deck, adding vehicle barriers in the passenger drop-off/pick-up parking area. based on type, and adding vehicle barriers in ready-to-load parking lots based on their class. Efforts that can be made by related parties are to build and increase the area of ​​basic land-side facilities needed at the Bolok Ferry Port.